Odpowiedź:
d)
(8 - 10x + 4x²) + (12x³ - 21x² - 6x) / (-3x) = 4x² - 10x + 8 - 4x² + 7x + 2 = -3x + 10
c)
(x² - 5x + 15) / (- 5) + (7 - 2x + 3x²) / 2 = -1/5x² + x - 3 + 7/2 - x + 3/2x² =
= -2/10x² + 1 5/10x² - 3 + 3 1/2 = 1 3/10x² + 1/2
b)
(x³ - 6x² + 8x) / (-2x) + (12 - 9x - 3x²) = -1/2x² + 3x - 4 + 12 - 9x - 3x² =
= -3 1/2x² - 6x + 8
a)
(x² - 6x + 18) / 3 + (x² - 3x + 5) / 2 = 1/3x² - 2x + 6 + 1/2x² - 3/2x + 5/2 =
= 2/6x² + 3/6x² - 3 1/2x + 7 1/2 = 5/6x² - 3 1/2x + 7 1/2
Szczegółowe wyjaśnienie: